Riding tandem: Does cycling infrastructure investment mirror gentrification and privilege in Portland, OR and Chicago, IL?. (December 2016) - Flanagan, Elizabeth; Lachapelle, Ugo; El-Geneidy, Ahmed
Abstract: Bicycles have the potential to provide an environmentally friendly, healthy, low cost, and enjoyable transportation option to people of all socio-demographic backgrounds. This research assesses the geographic distribution of cycling infrastructure with regard to community demographic characteristics to assess claims that cycling investment arrives in tandem with incoming populations of privilege or is targeted towards neighborhoods with existing socioeconomic wealth. Using census and municipal cycling infrastructure data in Chicago and Portland from 1990 to 2010, we create demographic and cycling infrastructure investment indices at the census tract level. Linear regressions estimate the extent to which existing community demographics and change in demographics associated with gentrification are related to cycling infrastructure investment. In both cities, we identify a bias towards increased cycling infrastructure investment in areas of existing or increasing privilege. This paper suggests that marginalized communities are unlikely to attract as much cycling infrastructure investment without the presence of privileged populations, even when considering population density and distance to downtown, two motivators of urban cycling. To alleviate the continuation of inequitable distributions of cycling investments, planning processes may actively seek out diverse stakeholders and be sensitive to citywide community input and stated needs in future transportation projects.